Ancient Greek Myth in World Fiction since 1989 - Hall, Edith (Bloomsbury Academic, 2016)
Ancient Greek Myth in World Fiction since 1989 explores the diverse ways that contemporary world fiction has engaged with ancient Greek myth. Whether as a framing device, or a filter, or via resonances and parallels, Greek myth has proven fruitful for many writers of fiction since the end of the Cold War. This volume examines the varied ways that writers from around the world have turned to classical antiquity to articulate their own contemporary concerns.Featuring contributions by an international group of scholars from a number of disciplines, the volume offers a cutting-edge, interdisciplinary approach to contemporary literature from around the world. Analysing a range of significant authors and works, not usually brought together in one place, the book introduces readers to some less-familiar fiction, while demonstrating the central place that classical literature can claim in the global literary curriculum of the third millennium.